1996
DOI: 10.1507/endocrj.43.429
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Activin in Normal Pituitary and in Various Human Pituitary Adenomas by Immunohistochemistry.

Abstract: Abstract. Inhibins and activins have been known to modify the secretion of various pituitary hormones. To study whether inhibins and activins are present in human pituitary tissues, immunohistochemical studies with antisera to activin A and inhibin a subunit were performed on 9 human pituitary adenoma tissue specimens and one sample of normal pituitary tissue adjacent to one adenoma. Activin immunoreactivities were demonstrated in the cytoplasms of one GH and one PRL and two nonfunctioning adenomas and one nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Moreover, inhibin and activin have been demonstrated immunohistochemically in various types of pituitary adenomas [4,30], but, as far as we know, there are no reports regarding the identification of these peptides in tumours of the gastro-entero-pancreatic endocrine system.…”
Section: And R O L E S : Stefano La Rosa · Silvia Uccella · Paola Billomentioning
confidence: 99%
“…Moreover, inhibin and activin have been demonstrated immunohistochemically in various types of pituitary adenomas [4,30], but, as far as we know, there are no reports regarding the identification of these peptides in tumours of the gastro-entero-pancreatic endocrine system.…”
Section: And R O L E S : Stefano La Rosa · Silvia Uccella · Paola Billomentioning
confidence: 99%
“…Indeed, TGF-β superfamily members, notably Activin and BMP, have been reported to exert regulatory functions in embryonic and adult pituitary gland (Bilezikjian et al 2006) but have also been implicated in the pathogenesis of human pituitary adenomas , Uccella et al 2000, Takeda et al 2003). Yet Activin expression is found in all pituitary tumours (Alexander et al 1995, Demura et al 1996, little was known, until now, about the impact on their signalling in prolactinomas and the underlying mechanism of their action through ALK4 and ALK7 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Reported detection of ActivinA and ActivinB in prolactinomas (Alexander et al 1995, Demura et al 1996 led us to investigate the expression of their cognate receptor ALK7 in prolactinomas. To do so, we took advantage of the well-established SMtTW3 prolactinoma model based on the allograft of a spontaneous prolactin transplantable tumour from Wistar/Furth Rat (Trouillas et al 1990).…”
Section: Alk7 Expression and Its Downstream Smad Signalling Is Inducementioning
confidence: 99%
See 1 more Smart Citation
“…EGF potently stimulates PRL expression (Murdoch et al 1982) and overexpression of EGF and EGF-R was found in seven lactotroph adenomas (LeRiche et al 1996). Activin, a TGF-β-related cytokine and the type I and type II activin TGF-β receptors have been shown to be abundant in human prolactinomas (Alexander et al 1995, 1996, Demura et al 1996. TGF-α colocalizes with PRL in lactotrophs in the normal pituitary and in PRL-secreting adenomas (Kobrin et al 1987).…”
Section: Pathogenesismentioning
confidence: 99%